2020
DOI: 10.21203/rs.3.rs-52894/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-636 inhibits EMT, cell proliferation and cell cycle of ovarian cancer by directly targeting transcription factor Gli2 involved in Hedgehog pathway

Abstract: Background: Hedgehog (Hh) signaling pathway, which is essential for cell proliferation and differentiation, is noted to be aberrantly activated in tumor from increasing studies in recent years. MicroRNAs (miRNAs) as an important non-coding RNA in cells have been proven to possess a regulatory role specific to the Hh signaling pathway. Here, in vitro and in vivo cellular/molecular experiments were adopted to clarify the regulatory mechanism linking miR-636 to the Hh signaling pathway in ovarian cancer (OVC). Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…26 Next, we searched the potential targets of circ_0010235 and validated that miR-636 was directly targeted by circ_0010235. MiR-636 plays a tumor-promoting or tumor-suppressing role in different cancer, acting as a tumor inhibitor in cervical cancer and ovarian cancer 27,28 and a promoter in bladder cancer. 29 In lung cancer, interference of circ_100876 suppressed lung cancer progression via regulating miR-636/ RET axis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Next, we searched the potential targets of circ_0010235 and validated that miR-636 was directly targeted by circ_0010235. MiR-636 plays a tumor-promoting or tumor-suppressing role in different cancer, acting as a tumor inhibitor in cervical cancer and ovarian cancer 27,28 and a promoter in bladder cancer. 29 In lung cancer, interference of circ_100876 suppressed lung cancer progression via regulating miR-636/ RET axis.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is bta-miR-26a which also reduced the abundance of PCK1 [44,45]. Moreover, the oncosuppressor miR-20a-3p was identified in melanoma, tongue squamous cell carcinoma, and hepatocellular carcinoma, and the oncosuppressor miR-636 was also identified in lung cancer, nasopharyngeal carcinoma, cervical cancer, endometrial cancer, ovarian cancer, and hepatocellular carcinoma [46][47][48][49][50][51][52][53][54][55][56]. It was reported that high miR-20a-3p and miR-636 expression were correlated with poor OS of CRC patients and this was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, circPTPRA can play opposite roles in different tumors, which may be related to tumor heterogeneity. Studies have reported that miR-636 acts as a tumor suppressor [30] or oncogene [29] in other tumors, but its role in PDAC is unclear. IGF2BP1 promotes PDAC cell proliferation by activating AKT, which can be used as a driver and a therapeutic target in PDAC [31].…”
Section: Discussionmentioning
confidence: 99%